2022
DOI: 10.1158/1078-0432.ccr-21-2918
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CD137+ T Cells Correlate with Improved Response to Anti-PD1 Immunotherapy in Patients with Cancer

Abstract: The introduction of immunotherapy in the treatment of cancer patients highlighted the critical role of patients' immune fitness for successful immunotherapy. Patients with a better or less dysregulated immunity appeared to have a better clinical outcome after the immunological treatments. We proposed the CD137 + T cell subset as a marker to define the "quality" of the immune activation of cancer patients able to predict the clinical outcome independently of tumor histotype and previous therapies. We believe th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…In addition, hypoxia-induced secretion of sCD137 from tumor cells blocks CD137-CD137L costimulation to achieve immune escape (30). A recent study showed that a high level of sCD137 predicts a poor response to immunotherapy (31), which is consistent with our finding that patients with low baseline sCD137 levels were more likely to respond to neoadjuvant immunochemotherapy. Tregs play a central role in maintaining immune tolerance and immunopathogenesis and functionally suppress various types of effector lymphocytes, such as CD4+ T helper cells and CD8+ cytotoxic T cells (32,33).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, hypoxia-induced secretion of sCD137 from tumor cells blocks CD137-CD137L costimulation to achieve immune escape (30). A recent study showed that a high level of sCD137 predicts a poor response to immunotherapy (31), which is consistent with our finding that patients with low baseline sCD137 levels were more likely to respond to neoadjuvant immunochemotherapy. Tregs play a central role in maintaining immune tolerance and immunopathogenesis and functionally suppress various types of effector lymphocytes, such as CD4+ T helper cells and CD8+ cytotoxic T cells (32,33).…”
Section: Discussionsupporting
confidence: 91%
“… 31 , 32 , 33 Considering the urgent clinical need to identify patients with rapid and durable response or resistance to treatment, CDK4/6i-induced immune modulation could be further evaluated as an innovative predictive factor. Indeed, changes in the circulating immune profile and tumoural immune microenvironment have been shown to be strongly related 34 , 35 , 36 and immune-profiling can become a powerful tool to provide prompt aid to therapeutic choice. 36 We cannot exclude the fact that the tumour burden reduction induced by CDK4/6i treatment could indirectly account for the Treg decrease observed in this study, by generally relieving the immunosuppressive status.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, changes in the circulating immune profile and tumoural immune microenvironment have been shown to be strongly related 34 , 35 , 36 and immune-profiling can become a powerful tool to provide prompt aid to therapeutic choice. 36 We cannot exclude the fact that the tumour burden reduction induced by CDK4/6i treatment could indirectly account for the Treg decrease observed in this study, by generally relieving the immunosuppressive status. A more focused study would be necessary to confirm the mechanism underlying our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD137 receptor, upregulated in T cells following activation [ 30 ], was associated, when expressed in CD8 and CD4 TILs, with clinical response to ICB [ 31 ]. In the circulation, CD137 expression in CD8, but not in CD4 T cells, was predictive of clinical responses [ 31 , 32 ]. Nonetheless, it would be of interest to assess the correlation between the expression of CD137 and of CD39 as well as their co-expression profile in circulating CD4 T cells and its possible association with patient responsiveness to ICB.…”
Section: Discussionmentioning
confidence: 99%